Niobium Modification of Au/CeO2 for Enhanced Catalytic Performance over Benzene Combustion - Zhe Liu; Xiaolan Zhang; Ting Cai; Jing Yuan; Kunfeng Zhao; Wenquan Lu; Dannong He (Nanomaterials, 2021)
A novel Au/Nb-CeO2 was obtained by loading Au to Nb-modified CeO2 adopting a thermal decomposition method. The modification effect of Nb on the physicochemical properties and performance of Au/CeO2 for benzene combustion was systematically clarified. The incorporated Nb species are found to be present in the two forms of highly-dispersed state and bulk NbOx into CeO2 lattice in the obtained Au/Nb-CeO2 catalyst. They greatly enlarged the BET surface area, improved the redox property, and strengthened the Au–support interaction. The addition of Nb also promotes catalytic performance of Au/CeO2, especially high-temperature performance: T90% decreases by ca. 40 °C and Au/Nb-CeO2 exhibits superior stability to Au/CeO2 at 230 °C. The slightly improved Au dispersion and redox properties resulted in the small increase on initial activity of Au/Nb-CeO2, but the large BET surface area and the strong Au–support interaction greatly promoted the high-temperature performance improvement of Au/Nb-CeO2 for benzene combustion reaction.